2008
DOI: 10.5558/tfc84511-4
|View full text |Cite
|
Sign up to set email alerts
|

Valuing multiple forest outputs

Abstract: In today's society, there is increasing pressure placed on forests to provide multiple forest outputs. Forestry organizations have responded by promoting identification and valuation of these outputs for trade-off, criteria and indicators, or other analyses. However, in the process of conducting such analyses, many forest outputs are dropped at the evaluation stage owing to a stated lack of available and reliable data. In an effort to help increase our understanding of the value of multiple forest outputs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…This could be achieved by a larger survey than the one conducted for this study, accompanied by factor analyses to reduce the number of items for use in subsequent surveys. Revision of the items to produce variables amenable to quantitative measurement (Lantz 2008) is another potential development. Additionally to investigating expectations, Tindall (2003) and Ford et al (2009) recommend investigating the underlying human beliefs.…”
Section: Natural Environment Values (Nev)mentioning
confidence: 99%
“…This could be achieved by a larger survey than the one conducted for this study, accompanied by factor analyses to reduce the number of items for use in subsequent surveys. Revision of the items to produce variables amenable to quantitative measurement (Lantz 2008) is another potential development. Additionally to investigating expectations, Tindall (2003) and Ford et al (2009) recommend investigating the underlying human beliefs.…”
Section: Natural Environment Values (Nev)mentioning
confidence: 99%
“…The majority of samples that are non-compliant are technical violations of the 0.1 μg/g default MRL for commodity/pesticide combinations for which Health Canada has not yet established an MRL (CFIA, 2015; 2017). Of particular concern to consumers are the twelve commodities, termed the dirty dozen, that are most often found to have multiple detectable pesticide residues on their surface (Lantz, 2015). Apples are found at the top of the dirty dozen list and regulatory testing has shown that 73% of Canadian domestic and 88% of imported apples test positive for multiple surface residues on their way to market (it is important to note the distinction that these are detected residues, not residues exceeding the MRL) (CFIA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As we discussed this dichotomy, we realized that a key source of conflict was the multiple values that people hold for forests. Much has been written about forest values (e.g., Tindall 2003, Kant 2007, Lantz 2008, Moyer at al. 2008) but among us we had rather different ideas on what the term "forest value" meant.…”
Section: Terms Concepts and Clarificationsmentioning
confidence: 99%